1.15 Nickel-Catalyzed Nondirected C—H Functionalization - Nakao,Y. (Base-Metal Catalysis 1, 2023)
This chapter summarizes some selected examples of nickel-catalyzed nondirected C—H functionalization reactions. Nickel(0) complexes have been demonstrated to be effective for C—H alkylation and alkenylation reactions of arenes and hetarenes through a ligand-to-ligand hydrogen-transfer mechanism for C—H activation that is unique to nickel-catalyzed approaches. They also effect the C—H borylation of arenes and hetarenes. Some nickel(II) complexes are shown to catalyze cross-coupling-type transformations of hetarenes with organic electrophiles through C—H activation by nickel(II) intermediates.
Keywords: base-metal catalysis; C—H activation; C—H alkylation; C—H alkenylation; C—H arylation; C—H alkynylation; C—H borylation; C—H functionalization; nickel catalysis